Advance care planning for people with dementia: Ordinary everyday conversations. (November 2019) - de Vries, Kay; Drury-Ruddlesden, Jenny
Advance care planning for people with dementia has become a focus of dementia care policies in developed countries. In New Zealand, the framework for dementia care relies on the person with dementia having a level of competence to enable them to participate in the planning process. For people with dementia, it may be too late to initiate these discussions in terms of decision-making capacity. Consequently, decisions about end-of-life care for people with dementia are typically made by a family member who acts as a surrogate decision maker on behalf of the person with dementia. An exploratory qualitative study of 23 people who had been carers or provided support for a family member with dementia who had died within five years of the interview was undertaken. The overarching theme, 'ordinary everyday conversations', describes how informal conversations and discussions within the family relating to preferences at the end of life had been embedded in interactions within the families over years. Sub-themes revealed three important components enabling adherence to the prior wishes of the person with dementia through these conversations: knowing the person and belief in 'doing the right thing'; the importance of Wills and Enduring Power of Attorney; and negotiating unexpected encounters. There is potential for families to be well prepared for the time when they may need to make decisions for the person with dementia based on ordinary everyday conversation that take place within families and throughout life. This study also suggests that more innovative approaches to making a Will may provide an important vehicle for expressing advanced care wishes.